PRODUCTION SPHERE ECOLOGIZATION AND MODERN WAYS OF ITS DEVELOPMENT - Zhanna S. Tikhonova (Advanced Engineering Research)
Basic aspects of the interaction between nature, man and manufacture are presented. Development issues of production sphere ecologization by means of such directions as ecologization of the wildlife management, application of the industrial waste disinfection and utilization technologies, ecological innovations adoption, etc., are considered.